Non-state sovereign entrepreneurs and non-territorial sovereign organizations - Jurgen Brauer; Robert Haywood (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
We propose two new concepts, of non-state sovereign entrepreneurs and the non-territorial sovereign organizations they form, and relate them to issues pertaining to state sovereignty, governance failures, and violent social conflict over the appropriation of the powers that accrue to states in modern international law. The concepts deal with the rise of transboundary non-state actors, as they impinge on and aim to supplement or supersede certain powers of state actors. We provide examples to show that non-state sovereign entrepreneurs and their organizations already exist. We are interested in their potential role in conflict transformation.
Keywords: F53; F55; H80; K33; 330; entrepreneurship; non-state sovereign entrepreneur; non-state sovereign organization; non-governmental organization; conflict; war; civil war; violence; peace